(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Various ion channels and ion transport systems located in the inner membrane of the mitochondria play an important role in the processes of signal transmission, cell function and death in the cell. Due to the importance of the role of these ion-transport systems in cell function, the study of their control mechanisms is relevant. Mitochondrial ion transport systems are involved in intracellular Ca2+ - signaling, ion homeostasis, and a number of physiological processes